Modeling of Seadome as artificial reefs for coastal wave attenuation. (15th July 2015) - Srisuwan, Chatchawin; Rattanamanee, Payom
Abstract: A newly designed marine structure, referred to as Seadome, is introduced and evaluated for its capability for surface wave attenuation in the nearshore zone for coastal protection purposes. More than 2600 laboratory tests showed that a range of 20–80% of wave height reduction could be achieved by use of a standard array consisting of 5 shore-parallel rows of the Seadome. The structure performance was found to increase almost linearly following the structure height to water depth ratio and the incident wave steepness, and decreases exponentially as the relative wave length to structure width increases. Semi-empirical formulas were developed and tested for prediction of the performance. A process-based predictive model with wider applicability and provision for qualitative insights is also introduced for the prediction purpose. A comparison between the modeled results and laboratory data was found to associate with root-mean-square error and standard deviation both less than 10%. A nomogram is developed as a ready-to-use tool for a practical design of the Seadome. According to the chart, a structure height to water depth ratio greater than 0.7 and a relative wave length to structure width smaller than 2.5 would be minimally required to achieve a wave amplitude reduction of 50%. Abstract : Highlights: Newly designed Seadome structure for use as artificial reefs for coastal protection. 2625 laboratory tests showing 20–80% wave height reduction. New semi-empirical and process-based models for prediction of Seadome performance. Nomograph as a ready-to-use tool for designing and optimizing the Seadome. Relative structure height and width over 0.7 and 0.5 for 50% wave height reduction.